KOHESIVITAS SUAMI ISTRI DI USIA MADYA - Anindita, Diah; Bashori, Khoiruddin (HUMANITAS (Jurnal Psikologi Indonesia), 2012)
In the middle age, adjustment to developmental tasks will affect marital relationship. This study aimed to determine the cohesiveness of husband and wife who have entered middle adulthood, covering aspects of solidarity, marital satisfaction, interest, and affiliates and also the factors that affectthe cohesiveness of husband and wife when the marriage age of 20 years or more. Subjects are three pairs of husband and wife who are legally married for over 20 years and each individuals age between 40-60 years old. This qualitative research used the case study approach and collected data by semi-structured interviews and nonparticipant observation. The results showed that the cohesiveness of husband and wife owned in middle age is different in each pair. In the first couple showed low cohesion, high on the second couple, and medium for the third couple. In the third couple,there is a change before the peak of the conflict in mid-2011 by now. Factors that affect the cohesiveness of husband and wife in middle age is a social perception, social support, emotional regulation, a period of quiet in the middle ages, the intensity of togetherness, understanding of gender, temperament, and love.